Construct Validity and Psychometric Properties of the Hebrew Version of the City Birth Trauma Scale - Handelzalts, Jonathan E.; Hairston, Ilana S.; Matatyahu, Adi (Frontiers in Psychology, 2018)
As many as third of the women perceive their childbirth as traumatic and although prevalence rates vary between studies, around 2-5% of women in community samples may develop childbirth-related postpartum post-traumatic stress disorder (PPTSD). The City Birth Trauma Scale (BiTS) was developed to address the need for a DSM-5-based instrument that assesses PPTSD. The BiTS is a self-report questionnaire, which covers all DSM-5 PTSD criteria, including the four symptom clusters - re-experiencing, avoidance, negative mood and cognitions and hyperarousal symptoms. The present study aimed to describe the psychometric properties and validate the Hebrew version of the BiTS. 504 mothers of 0-12 months old infants were sampled using social media and the snowball method. Respondents completed an online survey consisting of a demographic questionnaire and the Hebrew versions of the BiTS, the impact of event scale-revised (IES-R), the Edinburgh postpartum depression scale (EPDS), and the Pittsburgh Sleep Quality Index (PSQI). The Hebrew BiTS demonstrated high internal consistency for the total scale (Cronbach α = 0.90) and good internal consistency (Cronbach's α = 0.75-0.85) for the subscales. An exploratory factor (EFA) analysis yielded a two-factors solution, accounting for 45% of variance, with general symptoms loaded on Factor 1, and childbirth-related symptoms loaded on Factor 2, with both factors demonstrating high internal consistency (Cronbach's α = 0.90, 0,85, respectively). High convergent validity for the symptom cluster subscales was demonstrated with the parallel IES-R subscales, EPDS and PSQI. A two-step cluster analysis indicated that dysphoric and hyperarousal symptoms best differentiated the severity of symptoms of respondents across measures. In sum, the Hebrew BiTS was psychometrically sound, indicating its utility for clinical and non-clinical research. The EFA and cluster analyses support the differentiation between symptoms of dysphoria and hyperarousal from trauma (i.e., childbirth) specific symptoms, suggesting that symptoms relating to specific aspects of the trauma differ qualitatively from general symptom in the phenomenology of PPTSD. Further research using clinical samples and comparing the BiTS to DSM-5 diagnosis using clinical interview is needed.